1999
DOI: 10.1080/0260293990240303
|View full text |Cite
|
Sign up to set email alerts
|

Discipline‐related Marking Behaviour Using Percentages: a potential cause of inequity in assessment

Abstract: This study set out to ascertain whether percentage mark distributions show evidence of discipline-related marking behaviour and, if so, to consider the implications of this for equity in assessment outcomes. Performance data were obtained for 10 subjects at seven English universities for 1993English universities for -94, 1994English universities for -95 and 1995. The data showed that mark distributions at universities using percentages may be categorised into three Types (A,B and C). Type A distributions (En… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 4 publications
1
28
0
Order By: Relevance
“…Yorke (2011) notes a tension within higher education more generally between "retention and completion (with their implications for institutional funding) and ... the need for academics to uphold standards" (p. 258). This concern in the context of mathematics may also relate to the tendency of mathematics to have a far wider mark distribution than other subjects being coupled with the need to map that wider range onto a similar set of degree classifications without serious imbalances (Bridges et al, 1999) Thus the lecturers in this sample feel they 'fall back' on questions which test memory and computation. This, paired with the ease of marking of memory and computational questions, seems to have driven the written examination to a test of reproduction and routine applications of techniques.…”
Section: Resultsmentioning
confidence: 99%
“…Yorke (2011) notes a tension within higher education more generally between "retention and completion (with their implications for institutional funding) and ... the need for academics to uphold standards" (p. 258). This concern in the context of mathematics may also relate to the tendency of mathematics to have a far wider mark distribution than other subjects being coupled with the need to map that wider range onto a similar set of degree classifications without serious imbalances (Bridges et al, 1999) Thus the lecturers in this sample feel they 'fall back' on questions which test memory and computation. This, paired with the ease of marking of memory and computational questions, seems to have driven the written examination to a test of reproduction and routine applications of techniques.…”
Section: Resultsmentioning
confidence: 99%
“…… the use of percentage scales leads to inequities that are hard to justify" [p.451]. Moving to European style grades should lessen such inequities for, as Bridges et al [1999] found, there is "evidence of discipline-related marking behaviour when percentages are used … (but that) … differences between subjects are less marked when grading systems are used" [p.298].…”
Section: Lessons For the Uk And The Eumentioning
confidence: 99%
“…However, some empirically based concern is starting to emerge. In a study across 10 subjects in seven English universities, Bridges et al (1999) found that the higher the qualitative content was, the narrower the distribution of marks tended to be. Thus, their main conclusion is that:…”
Section: Ensuring Reliable Assessmentmentioning
confidence: 99%